1992
DOI: 10.1002/j.1460-2075.1992.tb05031.x
|View full text |Cite
|
Sign up to set email alerts
|

GAC1 may encode a regulatory subunit for protein phosphatase type 1 in Saccharomyces cerevisiae.

Abstract: Elevated dosage of the GAC1 gene from the yeast Saccharomyces cerevisiae causes hyperaccumulation of glycogen whereas a gene disruption of GAC1 results in reduced glycogen levels. Glycogen synthase is almost entirely in the active, glucose 6‐phosphate‐independent, form in cells with increased gene dosage of GAC1 whereas the enzyme is mostly in the inactive form in strains lacking GAC1. GAC1 encodes an 88 kDa protein that is similar to the regulatory subunit (RG1) of phosphoprotein phosphatase type 1 (PP‐1) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
142
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(149 citation statements)
references
References 59 publications
7
142
0
Order By: Relevance
“…Interactions between PHO85 and type 1 protein phosphatase. Some mutations in the GLC7 gene, which encodes the catalytic subunit of a type 1 protein phosphatase potentially involved in glycogen synthase dephosphorylation, cause glycogen storage phenotypes similar to those of snf1 mutants, impaired glycogen accumulation, and a lowered glycogen synthase activity ratio (4,16,20,25,29,52). Two such alleles are glc7-1 and glc7 Y-170 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions between PHO85 and type 1 protein phosphatase. Some mutations in the GLC7 gene, which encodes the catalytic subunit of a type 1 protein phosphatase potentially involved in glycogen synthase dephosphorylation, cause glycogen storage phenotypes similar to those of snf1 mutants, impaired glycogen accumulation, and a lowered glycogen synthase activity ratio (4,16,20,25,29,52). Two such alleles are glc7-1 and glc7 Y-170 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that glycogen synthase is dephosphorylated by a type 1 phosphatase composed of the Glc7p catalytic subunit and a regulatory subunit encoded by GAC1 (20,52,64). It was previously shown that point mutations at any of the three Gsy2p phosphorylation sites restored glycogen accumulation in phosphatase mutants defective in either Glc7p or Gac1p (25).…”
Section: Discussionmentioning
confidence: 99%
“…One positive clone, now named pGAD-GLG2, expressed the 47 COOH-terminal amino acids of a protein encoded by what we ultimately designated GLG2 (for glycogenin-like gene). The characterizations of the other two positive clones, derived from genes PIG1 and PIG2 (for protein interacting with Gsy2p), will be described elsewhere; Pig1p and Pig2p have limited sequence identity with Gac1p (18). The partial GLG2 sequence at the time had no match in GenBank, and we went on to identify and sequence the entire GLG2 gene, which was located on chromosome X (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that both the TOR and Ras-cAMP pathways control glycogen homeostasis in cells (45)(46)(47). Part of this effect is due to the fact that Msn2/Msn4 regulates the transcription of a subset of genes required for glycogen synthesis (48,49).…”
Section: The Absence Of Either Tor1 or Ras2 Restores The Defects In Tmentioning
confidence: 99%